Data screening and reduction in interplanetary dust measurement by IKAROS-ALADDIN. Issue 6 (15th March 2017) - Hirai, Takayuki; Yano, Hajime; Fujii, Masayuki; Hasegawa, Sunao; Moriyama, Nobuhiro; Okamoto, Chisato; Tanaka, Makoto
Abstract: We describe data screening and reduction procedures for dust impact measurements performed by the Arrayed Large-Area Dust Detectors in INterplanetary space (ALADDIN) during its observation period of about 300 days in 2010–2011. The ALADDIN is a polyvinylidene fluoride (PVDF) -based in-situ dust impact detector onboard the IKAROS solar sail. Its main scientific objective is to reveal the distribution of dust particles larger than 10 μm in the interplanetary space between 0.72 AU and 1.1 AU with higher time-space resolution than any former in-situ dust detectors. Among the downlinked 4427 events, there were some apparent and potential non-impact events. After screening the non-impact events, 1773 events were identified as the most promising dust impact events. In order to deduce the mass of impacted dust particles from the downlinked amplitude value, dV, we investigated both analog and digital characteristics of the ALADDIN electronics. The analog response was assessed by laboratory impact experiments with the ALADDIN flight spares. According to the developed calibration estimate, the mass range of the impacted dust particles corresponding to the dynamic range of analog peak amplitude is from 6.3 × 10 - 14  kg to 1.2 × 10 - 11  kg (4–22 μm diameter at the density of 2.0 g/cm 3 ) at the typical impact velocity at 1 AU from the Sun. In addition, it was found that the digital characteristics, i.e., slow signal-sampling rate, leads a probabilistic effect on the interpretation of the recorded dV values. For an example, the data set of dV higher than 1 V at 1 AU from the Sun includes ∼ 50% of the true impact number of dust particles with masses of 1.4 × 10 - 11  kg, and ∼ 100% of the impacts with particle masses above 4.7 × 10 - 10  kg. Even though the ALADDIN has undetectable range in the detection of smaller particles due to the sampling effect, it was proven that the ALADDIN is well suited to observe the distribution of dust particles larger than 10 μm in the Earth-Venus region.